Factors contributing the usage of credit card among young adults / Nor Ernida Jaafar and Zuziana Md Said - Jaafar, Nor Ernida; Md Said, Zuziana (Faculty of Business and Management, 2013)
The title of this study is “Factors Contributing The Usage of Credit Card Among Young Adults”. Credit card is known as plastic money which is an essential mode of payment. It is much more safer than carrying cash. Rebecca (2012) stated that there are a number of negative side effects linked with the use of a credit card that can affect financial in the future such as overspending and debt overload. There are three independent variables involve in this study which are function, convenience and status. Whereas, as for the dependent variable is the usage of credit card among young adults. The objectives of the study include to measure the level of credit card usage among young adults, to identify the relationship between the function, convenience, status and the usage of credit card among young adults and to determine the most significant factors to the efficiency and effectiveness of using credit cards among young adults. In gathering the data, a set of questionnaires was distributed to the employees at BERNAS, Standard Chartered, Public Bank Berhad and Hospital Kuala Lumpur. This study used stratified random sampling in order to select 100 respondents as a sample. Then, the data were analyzed using the Statistical Package for Social Science (SPSS)Version 20.0. Moreover, the frequency analysis, descriptive analysis, reliability test, Pearson correlation and multiple linear regression were used for data analysis method. There is significant relationship between function, convenience, status and usage of credit card among young adults.